2014
DOI: 10.1007/s11214-014-0119-6
|View full text |Cite
|
Sign up to set email alerts
|

Hot Plasma Composition Analyzer for the Magnetospheric Multiscale Mission

Abstract: This paper describes the science motivation, measurement objectives, performance requirements, detailed design, approach and implementation, and calibration of the four Hot Plasma Composition Analyzers (HPCA) for the Magnetospheric Multiscale mission. The HPCA is based entirely on electrostatic optics combining an electrostatic energy analyzer with a carbon-foil based time-of-flight analyzer. In order to fulfill mission requirements, the HPCA incorporates three unique technologies that give it very wide dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
185
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 172 publications
(186 citation statements)
references
References 30 publications
(33 reference statements)
0
185
0
Order By: Relevance
“…At low latitudes, cold ions are very common, have a smaller gyroradius than the hot magnetosheath and magnetospheric ions, and remain magnetized down to smaller spatial scales. The physics at these scales is relevant for particle energization and the reconnection rate [Drake et al, 2008;Yamada et al, 2010;Liu et al, 2014]. This is somewhat similar to the larger scale introduced by heavy ions [Shay and Swisdak, 2004;Markidis et al, 2011].…”
Section: Introductionmentioning
confidence: 82%
“…At low latitudes, cold ions are very common, have a smaller gyroradius than the hot magnetosheath and magnetospheric ions, and remain magnetized down to smaller spatial scales. The physics at these scales is relevant for particle energization and the reconnection rate [Drake et al, 2008;Yamada et al, 2010;Liu et al, 2014]. This is somewhat similar to the larger scale introduced by heavy ions [Shay and Swisdak, 2004;Markidis et al, 2011].…”
Section: Introductionmentioning
confidence: 82%
“…MMS will use an Active Spacecraft Potential Control device (ASPOC), which emits indium ions to neutralize the photoelectron current and keep the spacecraft from charging to more than four volts positive (Torkar et al 2014). Because physical processes in the ion diffusion region depend sensitively on ion mass, MMS includes a new-generation Hot Plasma Composition Analyzer (HPCA) (Burch et al 2005;Young et al 2014), which corrects problems with high proton fluxes that have prevented accurate ion-composition measurements near the dayside magnetospheric boundary (Phan et al 2003).…”
Section: Mission Requirementsmentioning
confidence: 99%
“…Also listed in Table 1 is the SOC (Science Operations Center). Details of these mission elements are provided in other papers in this issue (Torbert et al 2014;Ergun 2014;Russell et al 2014;Lindqvist et al 2014;Pollock 2015;Mauk et al 2014;Blake 2015;Young et al 2014;Torkar et al 2014). The arrangement of the scientific payload of each spacecraft is shown in Fig.…”
Section: Instrument Descriptionsmentioning
confidence: 99%
“…Here, the electric field (panel j and blue traces in panels g-i) and FPI ion velocity data (red traces in panels g-i) are averaged to 1-Hz resolution (i.e., about the ion-gyro frequency). Proton velocity data obtained by the Hot Plasma Composition Analyzer (HPCA) instrument (Young et al 2014) are shown in 10-s resolution as black curves in panels g-i. The transient dipolarizations and the crossings of the current layers are associated with enhancements in the equatorward/Earthward plasma flows and in the dawn-to-dusk electric field (negative E D ), as represented in Fig.…”
Section: Observationsmentioning
confidence: 99%